Effects of strength exercise interventions on activities of daily living, motor performance, and physical activity in children and adolescents with leukemia or non-Hodgkin lymphoma: Results from the randomized controlled ActiveADL Study - Gaser, Dominik; Peters, Christiane; Oberhoffer-Fritz, Renate; Götte, Miriam; Feuchtinger, Tobias; Schmid, Irene; Haller, Bernhard; von Luettichau, Irene; Kesting, Sabine (Frontiers in Pediatrics, 2022)
Objectives: Pediatric patients with cancer experience impairments in muscle strength and physical activity (PA) that may reduce autonomy during hospitalization. To determine the effects of strength exercise interventions on the accomplishment of activities of daily living (ADLs), motor performance, and PA in children with leukemia or non-Hodgkin lymphoma, we randomly allocated patients (4–18 years) immediately after diagnosis into two exercise groups. Methods: The intervention group (IG; n = 21) received a specific strength training combined with a standard care exercise program, whereas the control group (CG; n = 20) was provided standard care exercise program without any targeted muscle strengthening. After the baseline visit, participants were followed-up three times until intensive treatment cessation. We assessed physical function limitations using the Activities Scale for Kids© (ASK) and Functional ADL Screen. Secondary outcomes were PA levels using accelerometer and motor performance as measured by MOON-test (Motor performance in pediatric oncology-test). Results: In both groups, ADL accomplishment had significantly increased (p <0.05). However, no significant between-group differences for ASK outcome were noted. Motor performance was reduced in all motor abilities. Conclusions: Both exercise interventions were effective to maintain ADLs and motor performance during intensive treatment. In comparison, regular strength exercise interventions in the course of therapy tended to be more beneficial with regards to muscular explosive and endurance strength.